2015
DOI: 10.1186/s12876-015-0281-7
|View full text |Cite
|
Sign up to set email alerts
|

I-131 remnant ablation after thyroidectomy induced hepatotoxicity in a case of thyroid cancer

Abstract: BackgroundRadioactive iodine (I-131) is routinely used for the treatment of differentiated thyroid cancer following surgery. Drug-induced liver injury (DILI) is a leading cause of acute liver failure. Here we reported a rare case of diffuse hepatic uptake (DHU) of radioactive iodine (I-131) induced hepatotoxicity in patient with I-131 ablation therapy after thyroidectomy.Case presentationA 57-year-old woman was admitted due to jaundice, itching and dark urine with abnormally elevated liver function. She has pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Few previous studies have reported on DILI after iodine-131 therapy. Lin et al [ 4 ] reported hepatotoxicity after iodine-131 therapy in a patient with thyroid cancer who subsequently responded to methylprednisolone. Another report described two cases of liver toxicity after iodine-131 ablation therapy in two patients with Grave’s disease, both of whom were treated with prednisolone [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few previous studies have reported on DILI after iodine-131 therapy. Lin et al [ 4 ] reported hepatotoxicity after iodine-131 therapy in a patient with thyroid cancer who subsequently responded to methylprednisolone. Another report described two cases of liver toxicity after iodine-131 ablation therapy in two patients with Grave’s disease, both of whom were treated with prednisolone [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conventional doses of iodine-131 are 75–100 millicurie (mCi; 2,775–3,700 millibecquerel) [ 3 ]. Few case reports have found that iodine-131 induced liver injury, including a case report involving a patient with Grave’s disease [ 4 , 5 ]. Here we present a case of drug-induced liver injury (DILI) that occurred 10 days after iodine-131 ablative therapy and responded favorably to oral corticosteroid.…”
Section: Introductionmentioning
confidence: 99%
“…However, I-131 tends to accumulate in the stomach as it is orally administered and excreted by the urinary system [6]. Unfortunately, I-131 causes the destruction of thyroid cells through beta particles after the radioiodine is absorbed by the body fluids [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In I-131 treatment, the dosage prescribed for thyroid cancer is approximately 3,000 MBq, and the dosage may be increased to 8,000 MBq in patients with metastatic lesions [7][8][9]. As for patients are injected with large amounts of I-131, patients may have gastrointestinal adverse effects, including dose-dependent, presenting as nausea, anorexia, and vomiting [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In animal studies, it has been shown that RAIT caused significant morphological damage to rat livers in both short and long-term period of treatment [9,10]. It has been observed that the high dose RAI ablation therapy as 75–150 mCi might lead to drug-induced liver injury (DILI) in the thyroidectomized patient [11]. Liver toxicity has been reported even after low dose (5–10 mCi) 131 I treatment in two patients with Graves’ disease by Jhummon et al .…”
Section: Introductionmentioning
confidence: 99%